Impact of North Atlantic Tripole and Extratropical North Pacific Extreme SSTs on the 2023/24 El Niño - Chi‐Cherng Hong; Arnold Sullivan; Chih‐Chun Chang (Geophysical Research Letters)
Abstract Observations revealed notable discrepancies in the 2023/24 El Niño compared to earlier events, despite registering moderate Niño3.4 index magnitudes. Essential indicators such as the westerly wind burst, thermocline zonal tilting, and eastward propagation of oceanic Kelvin waves were conspicuously weak, indicating a weak air‐sea coupled in contrast to past occurrences, the 2023/24 El Niño coincided with unusually high North Atlantic Tripole and extratropical North Pacific sea surface temperatures (SSTs). The elevated North Atlantic Tripole SST triggered a strong negative Pacific meridional mode and easterly anomalies in the equatorial western‐central Pacific. At the same time, the extratropical North Pacific SST induced a negative Pacific Decadal Oscillation‐like pattern. These anomalies potentially dampened SST‐wind coupling during the developmental stages of El Niño. The negative Pacific meridional mode distinguished the 2023/24 El Niño from previous events and substantially altered its local and remote influences.